Optimal dilation time for combined small endoscopic sphincterotomy and balloon dilation for common bile duct stones: A multicentre, single-blinded, randomised controlled trial - Yıldırım, A. Emre (Turkish Journal of Gastroenterology, 2019)
Abstract Cite this article as: Yıldırım AE. Optimal dilation time for combined small endoscopic sphincterotomy and balloon dilation for common bile duct stones: A multicentre, single-blinded, randomised controlled trial. Turk J Gastroenterol 2019; 30(7): 662-3.